Sustainable innovation and leadership in the treatment of medical waste in Porto Alegre/RS - Schiavi, Cristiano Sordi; Soares, Henrique Martins de; Silva, Tania Nunes da (Revista de Administração da UFSM, 2021)
Purpose – The general objective of the research is to analyze an innovation in the Health Services Waste Management System (Medical Waste) and its importance for sustainable development in hospitals in Porto Alegre, capital of the state of Rio Grande do Sul (RS), Brazil, through the discussion of the concepts of sustainable innovation and sustainable leadership. Design/methodology/approach – A qualitative case study was used as a research strategy, choosing an innovative entrepreneur in the development of technologies and management services for RSS, which already has two large hospitals as clients in Porto Alegre. Findings – The research results showed the compatibilization of his MW managing solution with the concept of sustainable innovation. Furthermore, the entrepreneur showed to contemplate the guidelines for leaders in sustainability in their proposal of sustainable innovation, aiding his clients to transform their organizational culture, towards sustainability. Research limitations/implications – As research limitations, it was not possible to visit hospitals, due to the pandemic caused by COVID-19, making it impossible to know the management of RSS in loco, nor interviewing environmental operators and managers. Practical implications - In practical terms, the study showed that the internal treatment of MW is relevant in maximizing economic, environmental and social gains. Social implications – The findings demonstrated a need for cultural change, on the part of hospitals, with regard to the treatment of MW. Originality/value – The value of the study is the originality of innovation in the treatment of RSS and its great importance for sustainable medical waste management.